2018
DOI: 10.1104/pp.18.00495
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis VAC14 Is Critical for Pollen Development through Mediating Vacuolar Organization

Abstract: Pollen viability depends on dynamic vacuolar changes during pollen development involving increases and decreases of vacuolar volume through water and osmolite accumulation and vacuolar fission. Mutations in to, the genes encoding phosphatidylinositol 3,5-bisphosphate [PI(3,5)P]-converting kinases, are male gametophyte lethal in Arabidopsis () due to defective vacuolar fission after pollen mitosis I, suggesting a key role of the phospholipid in dynamic vacuolar organization. However, other genetic components th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…However, it is unclear whether the persistent central vacuole in scp microspores is the cause or consequence of the delayed division. In a further example that is linked to phosphatidylinositol 3,5‐bisphosphate [PI(3,5)P 2 ] production, mutation of VAC14 , hinders vacuolar fission in microspores and division at PMI leading to pollen abortion (Zhang et al , ). These studies emphasize an important link between the genetic control of vacuolar reorganization and successful transition to PMI.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether the persistent central vacuole in scp microspores is the cause or consequence of the delayed division. In a further example that is linked to phosphatidylinositol 3,5‐bisphosphate [PI(3,5)P 2 ] production, mutation of VAC14 , hinders vacuolar fission in microspores and division at PMI leading to pollen abortion (Zhang et al , ). These studies emphasize an important link between the genetic control of vacuolar reorganization and successful transition to PMI.…”
Section: Discussionmentioning
confidence: 99%
“…FAB1B and FAB1D have complementary roles in the regulation of membrane recycling, vacuolar pH, and the homeostatic ROS control in pollen tube growth, despite the cytosolic localization of FAB1D in the pollen tube (Serrazina et al., 2014). Unlike the gene arrangement of FAB1, Arabidopsis has a single VAC14 gene (Zhang et al., 2018). Bimolecular fluorescence complementation has revealed that FAB1A/B and VAC14 physically interact to form a functional protein complex in Arabidopsis (Whitley et al., 2009; Hirano et al., 2011; Zhang et al., 2018).…”
Section: Structures Of Fab1/pikfyve Complexes In Yeast Mammals and mentioning
confidence: 99%
“…Unlike the gene arrangement of FAB1, Arabidopsis has a single VAC14 gene (Zhang et al., 2018). Bimolecular fluorescence complementation has revealed that FAB1A/B and VAC14 physically interact to form a functional protein complex in Arabidopsis (Whitley et al., 2009; Hirano et al., 2011; Zhang et al., 2018). The Arabidopsis genome includes 9 SAC-domain containing phosphatase (SAC1-SAC9) genes (Zhong and Ye, 2003) which can be separated into three different classes based on their homology; SAC1-SAC5 are the most similar to yeast FIG4p, SAC6-SAC8 have two C-terminal transmembrane domains and are the most similar to yeast SAC1p, and SAC9 is the largest protein containing a unique WW domain (Zhong and Ye, 2003) (Figure 1).…”
Section: Structures Of Fab1/pikfyve Complexes In Yeast Mammals and mentioning
confidence: 99%
See 2 more Smart Citations